(untitled) (Research, Society and Development, 2024)
The complete gestation period can vary between 37 and 42 weeks. A baby is considered extremely premature when born at less than 28 weeks of gestation, very premature between 28 and 32 weeks, and moderately to late premature when born between 32 and 36 weeks. The objective of this study was to understand the relationship between the neuropsychomotor development of preterm and full-term babies and biopsychosocial aspects. The method is an integrative literature review. With the results of the first table, it is possible to observe that 9 articles were detailed, covering three categories of analysis: social factors, psychological factors, and biological factors, which can interfere with the development of preterm and full-term newborns. With the results of the second table, 8 articles were analyzed, identifying three categories of analysis: care for the puerperal woman, care for the preterm newborn in a hospital environment, and care for the full-term newborn. These categories can influence the elaboration of the nursing care process for both preterm and full-term babies and mothers. Therefore, the importance of future research is highlighted, which can demonstrate the results obtained, through interviews with nurses, physicians and other health professionals who provide care to premature and full-term babies.